PENGARUH EDUKASI SEKS PRANIKAH TERHADAP PENGETAHUAN DAN SIKAP SISWA DI SMK PGRI PEDAN KLATEN - Prasetyawati, Lutfika; Haryanti, Titik; Setyo Nugroho, Farid (Universitas Veteran Bangun Nusantara, 2023)
Based on data from the Directorate General of the Central Religious Courts in 2022, there were 52,094 cases of applications for dispensation among teenagers aged (15-19 years), of which 210 cases were in Klaten Regency. Dispensation cases are triggered by untimely accidents which originate from insufficient knowledge and attitudes regarding sex before marriage. The aim of this research is to determine the effect of sex before marriage education on students' knowledge and attitudes towards sex before marriage at SMK PGRI Pedan Klaten